2021
DOI: 10.1007/s11010-021-04240-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C for sepsis intervention: from redox biochemistry to clinical medicine

Abstract: Vitamin C, also known as ascorbic acid or ascorbate, is a water-soluble vitamin synthesized in plants as well as in animals except humans and several other animal species. Humans obtain vitamin C from dietary sources and via vitamin supplementation. Vitamin C possesses important biological functions, including serving as a cofactor for many enzymes, acting as an antioxidant and anti-inflammatory compound, and participating in regulating stem cell biology and epigenetics. The multifunctional nature of vitamin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 98 publications
(121 reference statements)
1
12
0
Order By: Relevance
“…Sepsis is a systemic inflammatory syndrome caused by potential or known infectious factors, and its progression can lead to shock and multiple organ dysfunction, which is the main cause of death in ICU patients. Despite extensive research on molecular pathogenesis based on targeted therapies, survival rates for severe sepsis and septic shock have not improved significantly (16). In recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is a systemic inflammatory syndrome caused by potential or known infectious factors, and its progression can lead to shock and multiple organ dysfunction, which is the main cause of death in ICU patients. Despite extensive research on molecular pathogenesis based on targeted therapies, survival rates for severe sepsis and septic shock have not improved significantly (16). In recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, clinical trials have reported that intravenous vitamin C reduces the organ function damage caused by sepsis and improves survival (15), and it has been demonstrated that parenteral vitamin C administration reduces organ injury and improves the survival of septic mice (16). However, the precise role of vitamin C as a neoadjuvant in sepsis and septic shock therapy is more controversial (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although vitamin E and C defi ciencies are rare, septic patients followed in the intensive care unit are known to have low plasma concentrations (20,21). The antioxidant activity and immunomodulatory effects of vitamins C and E are important in the functioning of the immune system and infl ammation mechanisms (22,23).…”
Section: A B C Dmentioning
confidence: 99%
“…Ascorbic acid (AA) is not only one of the essential nutrients for the human body, but also a good natural antioxidant which has been used as an additive in many commercial products. As one of the essential nutrients, AA plays vital roles in metabolism, body growth, development [11][12][13], antibody formation, iron absorption [14], folic acid and vitamin E stabilization. By scavenging free radicals, AA can prevent cardiovascular diseases, diabetes, and cancer.…”
Section: Introductionmentioning
confidence: 99%